Aqueous lithium battery positive electrode adhesive, preparation method and application

By preparing the lithium battery positive electrode adhesive into a core-shell structure, and reasonably setting the mass percentage of monomers and polar groups, the existing adhesives in lithium batteries have solved the problems of low bond strength, high internal resistance and environmental protection in lithium batteries, and the efficient and environmentally friendly positive electrode adhesive effect of lithium battery is achieved.

CN119592265APending Publication Date: 2025-03-11CHENGDU CODYYA TECHNOLOGY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411701245.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Existing lithium battery positive electrode adhesives such as PVDF have low bonding strength, easy structure collapse and powder loss, swelling and dissolution in organic electrolytes increase internal resistance, chemical reaction with lithium leads to thermal runaway, and the use of organic solvent NMP leads to high costs and environmental protection problems.

Method used

Using an aqueous lithium battery positive electrode adhesive, the adhesive is prepared into a core-shell structure, and the mass percentage of acrylate monomers, polar groups, etc. in the core layer structure and shell structure is reasonably set to achieve excellent bonding, wetting properties, high peel strength and low glass transition temperature of the adhesive.

Benefits of technology

It significantly improves the toughness and electrical properties of the adhesive, enhances the tolerance to the electrolyte, reduces production costs, simplifies the process, avoids environmental protection problems, and improves the safety and cycle life of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005153354060000071
    Figure BDA0005153354060000071
  • Figure BDA0005153354060000081
    Figure BDA0005153354060000081
  • Figure BDA0005153354060000082
    Figure BDA0005153354060000082
Patent Text Reader

Abstract

The invention discloses a water-based lithium battery positive electrode adhesive, a preparation method and application. The adhesive is of a single-layer or multi-layer shell core-shell structure formed by polar monomers such as acrylic acid, acrylate monomers, cross-linking monomers, self-emulsifying monomers and water through core-shell emulsion polymerization; by controlling the mass percent of acrylate monomers, polar groups and the like in the core layer structure and the shell layer structure and selecting proper types and dosages of cross-linking monomers and self-emulsifying monomers, the adhesive has proper surface tension, shows excellent adhesion and wettability to the current collector, has high peel strength, and is suitable for the current collector. According to the present invention, the lithium ion battery pole piece has the low glass-transition temperature so as to ensure the high toughness, the high surface density, the excellent electrolyte resistance, the excellent electrical property, the excellent coating property and the like of the pole piece, and the raw materials are all non-fluorine materials so as not to produce hydrogen fluoride and other harmful gases during the lithium battery recovery; water is used as a solvent, recycling is not needed, environment friendliness and low carbon are achieved, the manufacturing process is simplified, and the application range is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives, and in particular, relates to an aqueous lithium battery positive electrode adhesive, a preparation method and an application thereof. Background Art

[0002] Lithium-ion battery is a secondary battery, mainly composed of positive electrode, negative electrode, separator, electrolyte and battery casing. It mainly relies on the movement of lithium ions between the positive and negative electrodes to work. Due to its advantages such as high energy density and excellent cycle life, it is widely used in energy storage power stations, new energy transportation, smart grids and portable electronic devices and other fields.

[0003] In the prior art, when preparing positive or negative electrode sheets, an adhesive is usually used to bond the main material to the current collector. Commonly used adhesives include polyvinylidene fluoride (PVDF), which has high chemical stability but has the following disadvantages:

[0004] (1) The bonding strength is relatively low, and the structure is prone to collapse and powder loss during battery charging and discharging; (2) It swells and dissolves in organic electrolytes to form gel, which increases the internal resistance of the battery; (3) The reaction heat released by the chemical reaction with lithium is twice that of fluorine-free adhesives, which can easily cause thermal runaway; (4) When used, it requires the organic solvent N-methylpyrrolidone (NMP) as a solvent, and solvent recovery is required, which is costly; (5) As a fluorine-containing material, it is easy to produce a large amount of hydrogen fluoride during the recycling process of lithium batteries, which damages the environment and is subject to environmental protection policies and export restrictions.

[0005] In short, PVDF is not an ideal environmentally friendly and efficient lithium battery adhesive material.

[0006] Therefore, there is an urgent need to develop an environmentally friendly adhesive with strong bonding ability, high toughness strength, excellent electrolyte tolerance and excellent electrical properties to improve the safety, environmental protection and low cost of lithium batteries.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide an aqueous lithium battery positive electrode adhesive. The adhesive is prepared into a core-shell structure and the mass percentages of acrylate monomers, polar groups, etc. in the core layer structure and the shell layer structure are reasonably set so that the adhesive has a suitable surface tension, exhibits excellent bonding and wetting properties to the current collector aluminum foil, high peel strength, and a low glass transition temperature to ensure the softness and high surface density of the electrode sheet, is resistant to electrolyte, has excellent electrical properties, has good coating properties, etc., and meets various technical needs in the working environment of the lithium battery.

[0009] To achieve the above object, the basic concept of the technical solution adopted by the present invention is: to provide an aqueous lithium battery positive electrode adhesive, which is formed into a single-layer or multi-layer core-shell structure by core-shell emulsion polymerization of polar monomers, acrylate monomers, cross-linking monomers, self-emulsifying monomers and solvents;

[0010] The mass of the acrylic acid ester monomer accounts for 40-70% of the total mass of the raw materials;

[0011] The mass of the acrylic acid ester monomer in the core layer structure accounts for 50-80% of the mass of the core layer raw material;

[0012] The mass of the acrylic acid ester monomer in the shell structure accounts for 0 to 20% of the mass of the shell raw material.

[0013] Furthermore, the mass of the acrylic acid ester monomer in the core layer structure accounts for 60-70% of the mass of the core layer raw material, preferably 60%;

[0014] The mass of the acrylic acid ester monomer in the shell structure accounts for 0-10% of the mass of the shell raw material, preferably 5%.

[0015] Alternatively, in the core-shell structure of the multi-layer shell, the mass percentage of the acrylic acid ester monomers in the shell structure from the inside to the outside accounts for the mass percentage of the raw materials of each shell layer in descending order.

[0016] Preferably, the acrylic acid ester monomer is selected from one or more combinations of isooctyl acrylate, hydroxyethyl acrylate, butyl acrylate, butyl methacrylate, and methyl methacrylate.

[0017] Furthermore, the glass transition temperature Tg of the adhesive is -30 to 30°C;

[0018] Preferably, the glass transition temperature Tg1 of the core layer structure is lower than the glass transition temperature Tg2 of the shell layer structure, and the difference between Tg1 and Tg2 is 50 to 150°C;

[0019] Preferably, Tg1 is -50 to 0°C, more preferably -30 to -20°C;

[0020] Preferably, Tg2 is 50 to 100°C, more preferably 80 to 90°C;

[0021] In the core-shell structure of the multi-layer shell, the glass transition temperature Tg2 of the shell structure from the inside to the outside can be controlled according to the design requirements.

[0022] In the above scheme, acrylate monomers are soft monomers with a low glass transition temperature. By controlling the mass percentage of acrylate monomers in the raw materials, the Tg of the adhesive is regulated so that the Tg of the adhesive is controlled between -30 and 30°C, which significantly improves the toughness of the adhesive and balances the mechanical properties and heat resistance of the adhesive. It can be made into an ultra-high surface density, and the weight of the aluminum foil current collector is reduced to the positive electrode material, thereby increasing the overall volume density of the lithium battery and increasing the capacity of the lithium battery.

[0023] By designing the adhesive into a core-shell structure and controlling the mass percentage of acrylate monomers in the core layer structure and the shell layer structure, the glass transition temperature of the core layer structure is made lower than the glass transition temperature of the shell layer structure, and the toughness of the core layer structure is better. When the positive electrode material is bonded to the current collector using the adhesive, during operation, as the temperature rises, the shell layer structure ruptures and releases the core layer structure to form a uniform film, thereby improving the coating performance, bonding performance and friction resistance of the adhesive. In addition, the high cross-linking density of the core layer makes up for the disadvantage that the polymer mainly composed of acrylates has poor tolerance to electrolytes, thereby ensuring the cycle life of the battery.

[0024] Furthermore, the raw material contains polar groups, and the mass of the polar groups accounts for 5 to 50% of the total mass of the raw material;

[0025] Preferably, the mass of the polar groups in the core layer structure accounts for 1 to 20% of the mass of the core layer raw material, preferably 3 to 6%;

[0026] Preferably, the mass of the polar groups in the shell structure accounts for 20-60% of the mass of the shell raw material, preferably 30-40%.

[0027] Furthermore, the polar group is selected from a combination of one or more of carboxyl, cyano, hydroxyl, amine, amide, modified amide, and sulfonic acid;

[0028] Preferably, the mass of the carboxyl groups accounts for 10-20% of the total mass of the raw materials;

[0029] Preferably, the mass of the carboxyl groups in the core layer structure accounts for 1 to 10% of the mass of the core layer raw material, preferably 3 to 6%;

[0030] Preferably, the mass of the carboxyl groups in the shell structure accounts for 10 to 50% of the mass of the shell raw material, preferably 20 to 30%.

[0031] In the above scheme, suitable adhesion is crucial for the adhesive, and the number of polar groups has a significant impact on the adhesive performance; in order to ensure that the adhesive has suitable adhesion, the proportion of polar groups is controlled to be 5-50%, and the adhesive has good moisture absorption resistance. Furthermore, the carboxyl group interacts with the amine group, amide group, and hydroxyl group to form hydrogen bonds, which produce strong adhesion, which is beneficial to improving the adhesive performance and electrolyte tolerance of the adhesive. Therefore, by limiting the proportion of carboxyl groups, the adhesive performance can be effectively improved, and the adhesive can also be ensured to have good fluidity, which is suitable for high-speed transfer coating process.

[0032] Furthermore, the mass of the polar monomer, the cross-linking monomer, and the self-emulsifying monomer accounts for 5-50%, 5-10%, and 1-8% of the total mass of the raw materials, respectively, preferably 30-40%, 4-6%, and 4-5%;

[0033] Preferably, the mass of the polar monomer, the cross-linking monomer, and the self-emulsifying monomer in the core layer structure accounts for 2-10%, 0-10%, and 1-8% of the mass of the core layer raw material, respectively, and preferably 4-6%, 5-6%, and 4-5%;

[0034] Preferably, the mass of the polar monomer, cross-linking monomer, and self-emulsifying monomer in the shell structure accounts for 10-50%, 0-5%, and 0-5% of the mass of the shell raw material, respectively, preferably 20-30%, 1-2%, and 2-3%;

[0035] Preferably, the polar monomer is selected from one or more combinations of acrylic acid, acrylonitrile, acrylamide, and hydroxyethyl acrylate;

[0036] Preferably, the solvent is water.

[0037] In the above scheme, by reasonably adjusting the mass proportions of polar monomers, cross-linking monomers, self-emulsifying monomers and solvents in the core layer structure and shell layer structure of the adhesive, and coordinating with acrylate monomers, the core layer structure and the shell layer structure have low Tg, which meet good bonding properties and high toughness, and solve the brittleness problem when a single polyacrylic acid is used as an adhesive. At the same time, polar groups such as carboxyl, cyano, hydroxyl, amine, and sulfonic acid groups are introduced. Through the selection and quality control of polar groups, the design and regulation of the surface tension of the adhesive are achieved, so that the adhesive can be fully attached to the surface of the current collector while having a suitable viscosity, and exhibits excellent bonding and wetting properties.

[0038] At the same time, all raw materials are non-fluorine materials, and no harmful gases such as hydrogen fluoride will be produced when lithium batteries are recycled, and will not be restricted by environmental protection policies; the adhesive is prepared with water as the solvent, and there is no need to recycle the solvent, which is environmentally friendly and low-carbon, and simplifies the preparation steps, post-processing and application processes.

[0039] Further, the crosslinking monomer is selected from one or more combinations of diacetone acrylamide (DAAM) / adipic dihydrazide (ADH), isobutyloxy acrylamide (IBMA), epoxy acrylate (GMA), methacryloxytrimethoxysilane (KH-550), and diallyl phthalate (DAP);

[0040] Preferably, the cross-linking monomer is a double cross-linking system selected from diacetone acrylamide / adipic dihydrazide and isobutoxy acrylamide, diallyl phthalate and isobutoxy acrylamide;

[0041] Preferably, the molar ratio of diallyl phthalate to isobutoxyacrylamide is (0.5-1):(0.5-1), more preferably 1:1.

[0042] In the above scheme, by adding a suitable cross-linking monomer, the emulsion is self-cross-linked at room temperature to form a three-dimensional network structure during polymerization. In this way, not only the high toughness and high adhesion of the low Tg are met, but also when immersed in the electrolyte, there is only a slight swelling without dissolution, thereby improving the electrolyte resistance of the adhesive, preventing the adhesive from dissolving into the electrolyte to cause the battery structure to collapse, blocking the micropores of the diaphragm, etc., resulting in deterioration of electrical performance and inability to be used normally, improving the stability of the adhesive and battery structure, and improving the long-term cycle characteristics of the battery.

[0043] In addition, the room temperature self-crosslinking effect of the double cross-linking system is obvious, which improves the adhesive's tolerance to the electrolyte. After the adhesive is formed into a film, the electrolyte absorption rate measured when immersed in an electrolyte at 60°C is less than 10%. It will not excessively swell or dissolve due to long-term contact with the electrolyte, thereby improving the life of the battery.

[0044] Furthermore, the self-emulsifying monomer is selected from a combination of one or more of sulfonates with double bonds, carboxylates with double bonds, and polyethers with double bonds;

[0045] Preferably, the sulfonate with double bonds includes at least allyl polyoxyethylene sulfonate and vinyl polyoxyethylene sulfonate; the carboxylate with double bonds includes at least acrylate; the polyether with double bonds includes at least allyl polyether and vinyl polyether;

[0046] Preferably, the self-emulsifying monomer is selected from a mixture of sodium acrylate, allyl polyether and vinyl polyoxyethylene sulfonate, and the mixing ratio is:

[0047] Sodium acrylate: allyl polyether: vinyl polyoxyethylene sulfonate is (0~1): (0~10): (0~1).

[0048] In the above scheme, self-emulsifying monomers are selected to avoid the use of small molecule emulsifiers. This is because small molecule emulsifiers can move in the adhesive coating after being made into electrodes, and easily enter the electrolyte, causing damage to battery performance. Self-emulsifying monomers are more beneficial to battery performance than small molecule emulsifiers.

[0049] The adhesive has a solid content of 40%, a consistency of 1000-3000 cps, and a pH of 7-9.

[0050] The present invention also provides a method for preparing an aqueous lithium battery positive electrode adhesive, which is used to prepare an aqueous lithium battery positive electrode adhesive as described above, and the method comprises the following steps:

[0051] S1: polar monomers, acrylate monomers, crosslinking monomers, self-emulsifying monomers, initiators and solvents are taken according to the mass percentage of the core layer raw materials and dispersed at high speed to obtain a pre-emulsion, and the core layer emulsion A is obtained by polymerization;

[0052] S2: polar monomers, acrylate monomers, crosslinking monomers, self-emulsifying monomers and solvents are mixed and stirred according to the mass percentage of the shell layer raw materials to obtain a shell layer emulsion B;

[0053] S3: under set conditions, gradually dropping the shell layer emulsion B and the initiator into the core layer emulsion A for reaction, and obtaining a single-shell core-shell structure adhesive through post-treatment;

[0054] Alternatively, S2′: polar monomers, acrylic ester monomers, crosslinking monomers, self-emulsifying monomers and solvents are respectively dispersed at high speed according to the mass percentage of the shell raw materials from the inside to the outside to obtain at least two shell emulsions C from the inside to the outside;

[0055] S3′: From inside to outside, the shell layer emulsion C and the initiator are gradually added dropwise into the core layer emulsion A for reaction under set conditions, and a multi-layer core-shell structure adhesive is obtained through post-treatment.

[0056] Furthermore, step S1 includes:

[0057] Polar monomers, acrylic monomers, crosslinking monomers, self-emulsifying monomers and solvents are mixed and dispersed at high speed according to the mass percentage of the core layer raw materials to form a stable pre-emulsion, and the pre-emulsion and the initiator solution are added dropwise into a reactor containing an ammonium bicarbonate aqueous solution at a first reaction temperature, and the reaction is carried out for a period of time to obtain a core layer emulsion A;

[0058] Preferably, the first reaction temperature is 80-86°C, preferably 84°C;

[0059] Preferably, the reaction time is 1 to 3 hours, preferably 2 hours;

[0060] Preferably, stirring is performed during the reaction, and the stirring speed is 300 to 1000 r / min, preferably 500 to 600 r / min.

[0061] Furthermore, step S3 includes:

[0062] The shell layer emulsion B and the initiator solution are added dropwise into the core layer emulsion A respectively, and the temperature is raised to the second reaction temperature, and the temperature is kept for a period of time to react, and a single-layer core-shell structure adhesive is obtained through post-treatment;

[0063] Preferably, the second reaction temperature is 88-92°C, preferably 90°C;

[0064] Preferably, the reaction time is 0.5 to 2 h, preferably 1 h;

[0065] Preferably, stirring is performed during the reaction, and the stirring speed is 300 to 1000 r / min, preferably 500 to 600 r / min.

[0066] In the above scheme, at the first reaction temperature, the main reaction is acrylate, at which time the proportion of hydrophilic polar monomers is relatively small, and controlling the lower temperature can avoid the formation of gel; at the second reaction temperature, the main reaction is hydrophilic polar monomers, and a higher polymerization temperature is used to increase the polymerization conversion rate and shorten the reaction time.

[0067] Furthermore, step S3′ includes:

[0068] The innermost shell emulsion C and the initiator solution are added dropwise into the core emulsion A respectively, and the reaction is kept warm for a period of time to form a core-shell emulsion;

[0069] The prepared shell emulsion C and the initiator solution are sequentially added to the core-shell emulsion from the inside to the outside, and each shell emulsion C is kept warm for a period of time after being added, and the same process is repeated until the outermost shell emulsion C is added, and then the temperature is raised to the second reaction temperature, and the reaction is kept warm for a period of time, and a multi-shell core-shell structure adhesive is obtained through post-treatment;

[0070] Preferably, the second reaction temperature is 88-92°C, preferably 90°C;

[0071] Preferably, the heat preservation reaction time after adding each shell emulsion C is 0 to 1 hour, preferably 30 minutes;

[0072] Preferably, the time of heat preservation reaction after heating to the second reaction temperature is 0.5 to 3 hours, preferably 1 to 1.5 hours;

[0073] Preferably, stirring is performed during the reaction, and the stirring speed is 300 to 1000 r / min, preferably 500 to 600 r / min.

[0074] In the above scheme, high-speed stirring and dispersion can be performed during the preparation process, thus shortening the preparation time.

[0075] By designing the adhesive into a multi-layer core-shell structure and controlling the mass percentage of each raw material in the core layer structure and the shell layer structure, the glass transition temperature of the core layer structure is made lower than the glass transition temperature of the shell layer structure, and the toughness of the core layer structure is better. When the positive electrode material is bonded to the current collector using the adhesive, during operation, as the temperature rises, the shell layer structure is broken and the core layer structure is released to form a uniform film, thereby improving the coating performance, bonding performance and friction resistance of the adhesive. In addition, the high cross-linking density of the core layer makes up for the disadvantage that the polymer mainly composed of acrylates has poor tolerance to electrolytes, thereby ensuring the cycle life of the battery.

[0076] Furthermore, the post-treatment includes cooling to a certain temperature, adding a pH regulator, and continuing to stir the reaction for a period of time to obtain an adhesive;

[0077] Preferably, the temperature is lowered to room temperature to 50°C, preferably 40°C;

[0078] Preferably, the pH adjuster is selected from an aqueous solution of sodium hydroxide, lithium hydroxide, and ammonia water, more preferably sodium hydroxide;

[0079] Preferably, the pH is adjusted to 7-9, more preferably 7.5.

[0080] In the above scheme, the pH is adjusted mainly to improve the dispersion ability of the polymer on the main materials such as lithium iron phosphate and lithium manganese oxide powders after salt formation, thereby shortening the pulping time; and the storage stability of the emulsion is directly related to the pH. When the pH value is about 7.5, the storage stability is guaranteed to the greatest extent.

[0081] Furthermore, the present invention also provides an application of the aqueous lithium battery positive electrode adhesive as described above, which is used to bond the positive electrode slurry to the current collector to prepare a pole piece, wherein the surface density of the pole piece is 150 to 300 g / m 2 , peel force is 75N / m;

[0082] Preferably, the positive electrode slurry is prepared by mixing the original slurry and the binder solution in a mass ratio of 100:(2.5-10);

[0083] Preferably, the raw slurry is prepared by mixing lithium iron phosphate, conductive carbon black, dispersant and water in a mass ratio of 100:(0.5-1):0.4:59.6, and the solid content of the raw slurry is 63%.

[0084] In the above scheme, the prepared adhesive is mixed with the original slurry and then coated on the current collector to prepare a pole piece. Since the adhesive has high bonding strength, dispersion performance and toughness, and the appropriate surface tension design enables it to have good bonding and wetting properties on the current collector, when the original slurry is bonded to the current collector using the adhesive, it can form a uniform film to form an ultra-high surface density, has a high peeling force, and has excellent electrolyte resistance. The initial capacity, internal resistance, cycle performance, rate performance, high temperature performance, etc. of the lithium battery prepared from the pole piece are better than those of the same type of battery made of PVDF, and the low temperature performance is better.

[0085] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0086] 1. The present invention provides an aqueous lithium battery positive electrode adhesive. Polar groups such as carboxyl, cyano, hydroxyl, amino, and sulfonic acid groups are introduced into the adhesive system by selecting raw material monomers and controlling the ratio of each monomer. The surface tension of the adhesive is controlled by the design of specific polar groups, so that the adhesive has excellent bonding and wetting properties to the current collector aluminum foil, improves the bonding firmness and reliability, and has good wetting, dispersion and bonding capabilities for lithium iron phosphate, conductive carbon black, etc. The coating has strong cohesion, a wide range of applications, and high application flexibility.

[0087] 2. The adhesive provided by the present invention controls the mass percentage of acrylic acid ester monomers in the raw materials to achieve the regulation of the Tg of the adhesive, significantly improves the toughness of the adhesive, and can be made into an ultra-high surface density, so that the weight of the aluminum foil current collector is reduced and given to the positive electrode material, thereby increasing the overall volume density of the lithium battery and increasing the capacity of the lithium battery; at the same time, the adhesive is designed into a core-shell structure, and by regulating the Tg of the core layer structure and the shell layer structure, the film formation uniformity, coating performance, bonding performance, electrolyte immersion resistance and friction resistance of the adhesive are improved.

[0088] 3. The raw materials of the adhesive provided by the present invention are all non-fluorine materials. No harmful gases such as hydrogen fluoride will be generated when the lithium battery is recycled, and it will not be restricted by environmental protection policies. The adhesive is prepared with water as the solvent, replacing the oily solvents such as NMP used in traditional adhesives. There is no need to recycle the solvent, which is environmentally friendly and low-carbon, simplifies the preparation process, and is suitable for the preparation of various positive electrode plates.

[0089] 4. The adhesive provided by the present invention adopts a self-emulsifying monomer to replace the traditional small molecule emulsifier, so as to avoid the small molecule emulsifier remaining in the adhesive and migrating into the electrolyte to affect the battery performance; the double cross-linking system is used to improve the tolerance of the adhesive to the electrolyte. After the adhesive is formed into a film, the electrolyte absorption rate measured by immersing the adhesive in an electrolyte at 60°C is less than 10%, and the volume change rate is less than 5%. It will not cause excessive swelling or dissolution due to long-term contact with the electrolyte, thereby improving the life of the battery. DETAILED DESCRIPTION

[0090] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention is clearly and completely described below in conjunction with some embodiments. It can be understood by those skilled in the art that the following implementation is only used to explain the technical principle of the present invention and is not intended to limit the scope of protection of the present invention. For example, although the present application describes the steps of the method of the present invention in a specific order, these orders are not restrictive. Without departing from the basic principles of the present invention, those skilled in the art can perform the steps in different orders.

[0091] It should be noted that the test method for peeling force is:

[0092] Tape method: 3m test tape (model Scotch 600-Q33), 1 kg pressure pressed on the positive electrode coating surface, left naturally for 30 minutes; FBS-5D single-arm digital display tensile testing machine 180° peeling, take the average value of three samples.

[0093] Sample preparation conditions: lithium iron phosphate and conductive agent: glue (solid): water = 98:2:60, coating thickness 100-120 μm, the sample is baked at 120°C for 2 minutes and then placed in a drying dish for 24 hours before testing.

[0094] Example 1

[0095] This embodiment provides an aqueous lithium battery positive electrode adhesive, and the raw material composition is as follows in parts by weight:

[0096]

[0097]

[0098] The specific preparation process is:

[0099] (1) dispersing 4% acrylic acid, 2% acrylonitrile, 30% isooctyl acrylate, 10% methyl methacrylate, 2% methacryloxytrimethoxysilane, 2% isobutyloxyacrylamide, 2% allyl polyoxyethylene sulfonate, 4% vinyl polyether, and 40% water at a speed of 3000 r / min for 2 minutes to obtain a stable emulsion which is pumped into a high-level tank 1;

[0100] (2) Place the polymerization kettle in a constant temperature water bath at 84°C and add 2% ammonium bicarbonate and 80% water into the kettle;

[0101] (3) Dissolve 0.6% ammonium persulfate in 30% water and put it into the high-level tank 2;

[0102] (4) Add the raw materials in the header tanks 1 and 2 to the polymerization kettle simultaneously, add the raw materials in the header tank 1 at a constant speed over 30 minutes, and stop adding the raw materials in the header tank 2 after half of the raw materials have been added, and keep warm for 30 minutes;

[0103] (5) Mix 5 grams of acrylic acid, 5 grams of acrylonitrile, 4 grams of acrylamide, 5 grams of isooctyl acrylate, 1 grams of methacryloyloxytrimethoxysilane, and 1 grams of isobutyloxyacrylamide, and pump them into the header tank 1. At the same time, uniformly add the raw materials in the header tanks 1 and 2 to the polymerization kettle. Add the raw materials in the header tank 1 uniformly over 30 minutes, and keep one quarter of the raw materials in the header tank 2. After the addition is completed, keep the temperature for 30 minutes.

[0104] (6) Mix the remaining raw materials together and pump them into the high-level tank 1. At the same time, add the raw materials in the high-level tanks 1 and 2 to the polymerization kettle at a uniform speed. After 30 minutes of addition, immediately heat it to 90°C and keep it warm for 1 hour.

[0105] (7) The temperature was lowered to 40° C., and a solution of 10% sodium hydroxide and 15% water was slowly added over 10 minutes. The mixture was stirred for 30 minutes to obtain an adhesive having a three-layer core-shell structure with a solid content of 40% and a consistency of 1050 cps, with one core and two shells.

[0106] Example 2

[0107] This embodiment provides an aqueous lithium battery positive electrode adhesive, and the raw material composition is as follows in parts by weight:

[0108]

[0109]

[0110] The specific preparation process is:

[0111] (1) 3% acrylic acid, 10% acrylonitrile, 50% isooctyl acrylate, 4% allyl phthalate, 3% isobutoxy acrylamide, 2% allyl polyoxyethylene sulfonate, 3% vinyl polyether, and 40% water are dispersed at a high speed of 3000 r / min for 2 minutes to obtain a stable emulsion which is pumped into a high-level tank 1;

[0112] (2) Place the polymerization kettle in a constant temperature water bath at 84°C and add 2% ammonium bicarbonate and 80% water into the kettle;

[0113] (3) Dissolve 0.6% ammonium persulfate in 30% water and put it into the high-level tank 2;

[0114] (4) Add the raw materials in the header tanks 1 and 2 to the polymerization kettle simultaneously, add the raw materials in the header tank 1 at a constant speed over 30 minutes, and stop adding the raw materials in the header tank 2 after half of the raw materials have been added, and keep warm for 30 minutes;

[0115] (5) Mix the remaining raw materials together and pump them into the high-level tank 1. At the same time, add the raw materials in the high-level tanks 1 and 2 to the polymerization kettle at a uniform speed. After 30 minutes of addition, immediately raise the temperature to 92°C and keep it warm for 1 hour.

[0116] (6) The temperature was lowered to 40° C., and a solution of 10% sodium hydroxide and 15% water was slowly added over 10 minutes. The mixture was stirred for 30 minutes to obtain an adhesive having a double-layer core-shell structure with a solid content of 40% and a consistency of 900 cps, with one core and one shell.

[0117] Experimental Example 1

[0118] In this experimental example, based on Example 1, only the experimental conditions in Table 1 were changed, and other conditions remained unchanged, to obtain Examples 3-6 and Comparative Examples 1-3, and the properties of the prepared adhesives were tested. The test results are shown in Table 1:

[0119] Table 1

[0120]

[0121]

[0122] Result analysis:

[0123] As shown in Table 1, compared with Example 1, the mass percentage of the cross-linked monomer in the core layer structure of Comparative Example 1 is less than 5% of the mass percentage of the core layer raw material, and the obtained adhesive has a high electrolyte absorption rate and reduced peeling force. Therefore, in the present invention, it is preferred that the mass of the cross-linked monomer in the core layer structure accounts for 5-10% of the mass of the core layer raw material.

[0124] Compared with the comparative test, Comparative Example 3 shows that the higher the proportion of acrylate, even if the distribution of polar monomers and carboxyl groups in the core-shell is the same, the Tg of the obtained electrode is reduced and the softness of the electrode is improved, but the ability to withstand electrolyte immersion is seriously reduced and the peeling force is seriously deteriorated, affecting the overall performance of the battery.

[0125] Compared with Comparative Examples 1-3, the adhesive peeling force of Examples 1-6 is greater, indicating better bonding firmness and reliability, and the electrolyte absorption rate measured when immersed in an electrolyte at 60°C after film formation is lower, and the electrolyte immersion resistance is better, thereby increasing the battery life.

[0126] Experimental Example 2

[0127] In this experimental example, on the basis of Example 1, the percentage of polar groups in the total mass of raw materials, the mass percentage of carboxyl groups in the core layer structure and the shell layer structure in the core layer raw material and the shell layer raw material were changed, and other conditions remained unchanged to obtain Examples 7-10 and Comparative Examples 4-5, and the properties of the prepared adhesives were tested. The test results are shown in Table 2:

[0128] Table 2

[0129]

[0130] Result analysis:

[0131] It can be seen from Table 2 that the polar monomer content and the distribution of carboxyl groups in the core-shell determine the performance of the electrode. The higher the polar group content, the better the electrode peeling force, the better the electrolyte tolerance, and the better the fluidity of the slurry, but the flexibility of the electrode shows the opposite rule.

[0132] Experimental Example 3

[0133] In this experimental example, on the basis of Example 1, the type and amount of the crosslinking monomer were changed, and other conditions remained unchanged, to obtain Examples 11-16, and the properties of the prepared adhesives were tested. The test results are shown in Table 3:

[0134] Table 3

[0135]

[0136]

[0137] As can be seen from Table 3, when the cross-linking monomer is selected from one or more combinations of diacetone acrylamide (DAAM) / adipic dihydrazide (ADH), isobutyloxy acrylamide (IBMA), epoxy acrylate (GMA), methacryloyloxy trimethoxy silane (KH-550), and diallyl phthalate (DAP) defined in the present invention, it is possible to self-crosslink at room temperature during emulsion polymerization to form a three-dimensional network structure. In this way, not only the high toughness and high adhesion of low Tg are met, but also, when immersed in the electrolyte, there is only slight swelling without dissolution, thereby improving the electrolyte resistance of the adhesive, preventing the adhesive from dissolving into the electrolyte to cause the battery structure to collapse, blocking the micropores of the diaphragm, etc., resulting in deterioration of the electrical performance and inability to be used normally, improving the stability of the adhesive and the battery structure, and improving the long-term cycle characteristics of the battery.

[0138] Especially when the cross-linking monomer is a double cross-linking system of isobutyloxyacrylamide (IBMA) and diallyl phthalate (DAP), and the molar ratio of the two is 1:1, the prepared adhesive has higher bonding performance, lower liquid absorption rate, and higher electrolyte resistance, which can effectively ensure the stability of the battery structure, improve the long-term cycle characteristics of the battery, and increase the battery life.

[0139] Experimental Example 4

[0140] The adhesive prepared in Example 1 is applied to the positive electrode sheet of a lithium battery, specifically:

[0141] Example 17: Lithium iron phosphate, conductive carbon black, dispersant and water were mixed in a mass ratio of 100:1:0.4:59.6 to prepare a slurry with a solid content of 63%. The slurry and the binder solution were mixed in a mass ratio of 100:8 to prepare a positive electrode slurry. After mixing, the mixture was coated on a current collector aluminum foil to prepare a pole piece. The surface density of the pole piece was 296 g / m 2 , the peel force is 76N / m.

[0142] Example 18: Lithium iron phosphate, conductive carbon black, adhesive solid and water were mixed in a mass ratio of 100:1:8:59.6 and coated on a current collector aluminum foil to prepare a pole piece. The surface density of the pole piece was 296 g / m 2 , the peel force is 78N / m.

[0143] Experimental Example 5

[0144] Comparative Example 6: A conventional positive electrode sheet was prepared by replacing the adhesive in Example 15 with a commonly used positive electrode adhesive (PVDF) on the market and replacing the water in Example 15 with NMP.

[0145] In this experimental example, the pole pieces prepared in Example 17 and Example 18 and Comparative Example 6 were prepared into batteries according to the same main material ratio, and the performance of the prepared batteries was tested respectively. The test results are as follows:

[0146] (1) Battery discharge performance test at different rates:

[0147] Table 4

[0148]

[0149]

[0150] As can be seen from Table 4, the batteries prepared in Examples 17 and 18 have advantages in low-rate discharge performance and obvious advantages in high-rate discharge performance over the batteries prepared in the PVDF system in Comparative Example 6.

[0151] (2) Battery low temperature discharge performance test:

[0152] Test conditions: low temperature discharge at -20℃, 0.5c / 1c.

[0153] Table 5

[0154]

[0155] As can be seen from Table 5, the 0.5C / 1C experimental data of the batteries prepared in Example 17 and Example 18 are similar, but both have advantages over the battery prepared by the PVDF system in Comparative Example 6. The low-temperature discharge performance of Examples 15 and 16 is better than that of Comparative Example 6.

[0156] (3) Battery storage test:

[0157] Table 6

[0158]

[0159] It can be seen from Table 6 that the batteries prepared in Examples 17 and 18 have advantages over the battery prepared in the PVDF system in Comparative Example 6 in terms of high temperature storage performance.

[0160] (4) Battery cycle performance test:

[0161] Table 7

[0162]

[0163]

[0164] It can be seen from Table 7 that the batteries prepared in Examples 17 and 18 have obvious advantages in long cycle performance over the battery prepared in the PVDF system in Comparative Example 6.

[0165] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with the present invention can make some changes or modify the technical contents suggested above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the solution of the present invention.

Claims

1. A water-based lithium battery positive electrode adhesive, characterized in that: A core-shell structure with a single or multi-layer shell is formed by core-shell emulsion polymerization of polar monomers, acrylic ester monomers, crosslinking monomers, self-emulsifying monomers and solvents; The mass of the acrylic acid ester monomer accounts for 40-70% of the total mass of the raw materials; The mass of the acrylic acid ester monomer in the core layer structure accounts for 50-90% of the mass of the core layer raw material; The mass of the acrylic acid ester monomer in the shell structure accounts for 0 to 20% of the mass of the shell raw material.

2. The aqueous lithium battery positive electrode adhesive according to claim 1, characterized in that: The mass of the acrylic acid ester monomer in the core layer structure accounts for 50-80% of the mass of the core layer raw material; preferably 60-70%, preferably 60%; The mass of the acrylic acid ester monomer in the shell structure accounts for 0-10% of the mass of the shell raw material, preferably 5%; Preferably, the acrylic acid ester monomer is selected from one or more combinations of isooctyl acrylate, hydroxyethyl acrylate, butyl acrylate, butyl methacrylate, and methyl methacrylate.

3. The aqueous lithium battery positive electrode adhesive according to claim 1 or 2, characterized in that: The glass transition temperature Tg of the adhesive is -30 to 30°C; Preferably, the glass transition temperature Tg1 of the core layer structure is lower than the glass transition temperature Tg2 of the shell layer structure, and the difference between Tg1 and Tg2 is 50 to 150°C; Preferably, Tg1 is -50 to 0°C, more preferably -30 to -20°C; Preferably, Tg2 is 50 to 100°C, more preferably 80 to 90°C.

4. The aqueous lithium battery positive electrode adhesive according to any one of claims 1 to 3, characterized in that: The raw material contains polar groups, and the mass of the polar groups accounts for 5 to 50% of the total mass of the raw material; Preferably, the polar group is selected from a combination of one or more of carboxyl, cyano, hydroxyl, amine, amide, modified amide, and sulfonic acid; Preferably, the mass of the carboxyl groups accounts for 2 to 15% of the total mass of the raw materials; Preferably, the mass of the carboxyl groups in the core layer structure accounts for 1 to 10% of the mass of the core layer raw material, preferably 3 to 6%; Preferably, the mass of the carboxyl groups in the shell structure accounts for 10 to 50% of the mass of the shell raw material, preferably 20 to 30%.

5. The aqueous lithium battery positive electrode adhesive according to any one of claims 1 to 4, characterized in that: The mass of the polar monomer, cross-linking monomer and self-emulsifying monomer respectively accounts for 5-50%, 5-10% and 1-8% of the total mass of the raw materials, preferably 30-40%, 4-6% and 4-5%; Preferably, the mass of the polar monomer, the cross-linking monomer, and the self-emulsifying monomer in the core layer structure accounts for 2-10%, 0-10%, and 1-8% of the mass of the core layer raw material, respectively, and preferably 4-6%, 5-10%, and 4-5%; Preferably, the mass of the polar monomer, cross-linking monomer, and self-emulsifying monomer in the shell structure accounts for 10-50%, 0-5%, and 0-5% of the mass of the shell raw material, respectively, preferably 20-30%, 1-2%, and 2-3%; Preferably, the polar monomer is selected from a combination of one or more of acrylic acid, acrylonitrile, acrylamide, and hydroxyethyl acrylate; Preferably, the solvent is water; Preferably, the crosslinking monomer is selected from a combination of one or more of diacetone acrylamide / adipic dihydrazide, isobutoxy acrylamide, epoxy acrylate, methacryloxytrimethoxysilane, and diallyl phthalate; Preferably, the cross-linking monomer is a double cross-linking system selected from diacetone acrylamide / adipic dihydrazide and isobutoxy acrylamide, diallyl phthalate and isobutoxy acrylamide; Preferably, the molar ratio of diallyl phthalate to isobutoxyacrylamide is (0.5-1): (0.5-1); Preferably, the self-emulsifying monomer is selected from a combination of one or more of sulfonates with double bonds, carboxylates with double bonds, and polyethers with double bonds.

6. A method for preparing an aqueous lithium battery positive electrode adhesive, characterized in that: For preparing the aqueous lithium battery positive electrode adhesive according to any one of claims 1 to 5, the method comprises the following steps: S1: polar monomers, acrylate monomers, crosslinking monomers, self-emulsifying monomers, initiators and solvents are taken according to the mass percentage of the core layer raw materials and dispersed at high speed to obtain a pre-emulsion, and the core layer emulsion A is obtained by polymerization; S2: polar monomers, acrylate monomers, crosslinking monomers, self-emulsifying monomers and solvents are mixed and stirred according to the mass percentage of the shell layer raw materials to obtain a shell layer emulsion B; S3: under set conditions, gradually dropping the shell layer emulsion B and the initiator into the core layer emulsion A for reaction, and obtaining a single-shell core-shell structure adhesive through post-treatment; Alternatively, S2′: polar monomers, acrylic ester monomers, crosslinking monomers, self-emulsifying monomers and solvents are respectively dispersed at high speed according to the mass percentage of the shell raw materials from the inside to the outside to obtain at least two shell emulsions C from the inside to the outside; S3′: from inside to outside, the shell emulsion C and the initiator are gradually added dropwise into the core emulsion A under set conditions to react, and a multi-layer core-shell structure adhesive is obtained through post-treatment; Preferably, the post-treatment includes cooling to room temperature to 50° C., adding a pH regulator to adjust the pH to 7 to 9, and continuing to stir the reaction for 30 minutes to obtain the adhesive.

7. The method for preparing the aqueous lithium battery positive electrode adhesive according to claim 6, characterized in that: Step S1 includes: Polar monomers, acrylic monomers, crosslinking monomers, self-emulsifying monomers and solvents are mixed and dispersed at high speed according to the mass percentage of the core layer raw materials to form a stable pre-emulsion, and the pre-emulsion and the initiator solution are added dropwise into a reactor containing an ammonium bicarbonate aqueous solution at a first reaction temperature, and the reaction is carried out for a period of time to obtain a core layer emulsion A; Preferably, the first reaction temperature is 80-86°C, preferably 84°C; Preferably, the reaction time is 1 to 3 hours, preferably 2 hours.

8. The method for preparing the aqueous lithium battery positive electrode adhesive according to claim 7, characterized in that: Step S3 includes: The shell layer emulsion B and the initiator solution are added dropwise into the core layer emulsion A respectively, and the temperature is raised to the second reaction temperature, and the temperature is kept for a period of time to react, and a single-layer core-shell structure adhesive is obtained through post-treatment; Preferably, the second reaction temperature is 88-92°C, preferably 90°C; Preferably, the reaction time is 0.5 to 2 h, preferably 1 h.

9. The method for preparing the aqueous lithium battery positive electrode adhesive according to claim 7, characterized in that: Step S3′ includes: The innermost shell emulsion C and the initiator solution are added dropwise into the core emulsion A respectively, and the reaction is kept warm for a period of time to form a core-shell emulsion; The prepared shell emulsion C and the initiator solution are sequentially added to the core-shell emulsion from the inside to the outside, and each shell emulsion C is kept warm for a period of time after being added, and the same process is repeated until the outermost shell emulsion C is added, and then the temperature is raised to the second reaction temperature, and the reaction is kept warm for a period of time, and a multi-shell core-shell structure adhesive is obtained through post-treatment; Preferably, the second reaction temperature is 88-92°C, preferably 90°C; Preferably, the heat preservation reaction time after adding each shell emulsion C is 0 to 1 hour, preferably 30 minutes; Preferably, the reaction time after heating to the second reaction temperature is 0.5 to 3 hours, preferably 1 to 1.5 hours.

10. An application of the aqueous lithium battery positive electrode adhesive as claimed in any one of claims 1 to 5, characterized in that: Used to bond the positive electrode slurry to the current collector to prepare a pole piece, the surface density of the pole piece is 150-300g / m 2 , peel force is 75N / m; Preferably, the positive electrode slurry is prepared by mixing the original slurry and the binder solution in a mass ratio of 100:(2.5-10); Preferably, the raw slurry is prepared by mixing lithium iron phosphate, conductive carbon black, dispersant and water in a mass ratio of 100:(0.5-1):0.4:59.6, and the solid content of the raw slurry is 63%.

Citation Information

Cited By

  • High-energy-density self-repairing long-circulation positive pole piece, preparation method, application and lithium ion battery

    CN120432488A

  • Diaphragm binder, diaphragm and battery

    CN120795836A

  • Composite separator and secondary battery

    CN121906086A

  • Composite separator and secondary battery

    CN121906086B